The Essential Role of SIRT1 in Hypothalamic-Pituitary Axis - Yamamoto, Masaaki; Takahashi, Yutaka (Frontiers in Endocrinology, 2018)
The endocrine system plays an essential role in the physiological adaptation to malnutrition. The adaptive response of various hormones directs the energy utilization toward the survival functions and away from growth and reproduction. Particularly, the hypothalamic pituitary axis plays an integral and a central role in the regulation of endocrine organs. Sirtuin 1 (SIRT1) is a nicotinamide adenine dinucleotide (NAD)-dependent histone deacetylase that is activated in response to calorie restriction (CR). SIRT1 is involved in cellular processes via the deacetylation of histone as well as various transcription factors and signal transduction molecules and thereby modulates the endocrine/metabolic functions. Several evidence clearly demonstrate that SIRT1 in the hypothalamus, pituitary gland, and other target organs modifies the synthesis, secretion, and activities of hormones and in turn induces the adaptive responses. In this review, we discussed the role of SIRT1 in the hypothalamic pituitary axis and its pathophysiological significance.